The Severity of The Clinical Course of Gout in Metabolic Syndrome. - Kayumov U.K; Khatamova D.T; Saipova M.L; Musaeva Sh.Z; Ziyamukhamedova M.M. (Genius Journals, 2021)
The metabolic syndrome and insulin resistance in gout have been studied in only a few studies, showing the presence of the syndrome and its characteristic insulin resistance in the vast majority of patients the effects of insulin resistance and hyperinsulinemia on gout, in particular on joint syndrome and other clinical manifestations, have only been reported in a few studies. However, they have shown a high incidence of metabolic syndrome and its characteristic insulin resistance in an overwhelming number of gout patients A direct link has been found between certain components of the metabolic syndrome, in particular insulin resistance and hyperinsulinemia, and the severity of hyperuricemia, which is associated with a more severe course of gouty arthritis in gout patients.
Keywords: Metabolic syndrome; gout index severity; hyperglycaemia